Development Model of Improving the Role of Pregnant Women Husbands for Preventing Early Stunting in Regency Padang Pariaman in 2021 - Erpita Yanti; Yessy Aprihatin; Nurul hanifah (International Journal on Integrated Education, 2021)
The purpose of this study was to identify and prevent The incidence of early stunting in the working area of the health Center Lubuk Alung. The study used a research quasi-design experiment with a research design with a research pre and post-sample of 50 respondents. The results showed that there were differences in scores obtained from the results of the analy-sis Wilcoxon Sign Range Test. z = -4202A and p-value = 0,000, in the knowledge that means p-value <0.05 where H0 is rejected, the Ha accepted. On the Action obtained a score of -3 270a and p-value = 0,001 which means p-value <0.05 where H0 is rejected, the Ha accepted. It is expected that respondents will be able to maintain the increased role of pregnant women's husbands in preventing early stunting in the health Center Work Area Lubuk Alung. The results of the study showed that there was an increase in the role of husbands in preventing early stunting in the Lubuk Alung Health Center Work area. The results of the analysis showed that of the 50 respondents, 56% of respondents had a low level of knowledge and 44% had a high level of knowledge. When done post-test results showed a better chance that 22% of respondents have a low level of knowledge and 78% have a high knowledge level. This means that the level of knowledge before using the model application to increase the role of pregnant women's husbands for preventing early stunting has changed for the better than before using the application.